Mechanical characterization of the structural components of Pre-Columbian earthen monuments: Analysis of bricks and mortar from Huaca de la Luna in Perú - Aguilar, R.; Montesinos, M.; Uceda, S. (Elsevier, 2017)
The paper deals with the mechanical characterization of the materials that composes the structural system of the archaeological earthen complex of ‘Huaca de la Luna’ in Perú (100–900A.D.). The mechanical characterization was carried out through uniaxial compression, three-point bending and splitting tests. The results indicate differences in bricks and mortar samples in strength capacity and elastic stiffness in compression, as well as differences in rupture modulus and diametric compression strength. The study contributes to understand the linear and nonlinear behavior of archaeological earthen materials and structures and provides reference values for the structural assessment of similar buildings and monuments.
Keywords: Archaeological heritage; Earthen buildings; Bricks and mortar; Mechanical characterization; https://purl.org/pe-repo/ocde/ford#2.01.04